NusG is required to overcome a kinetic limitation to Rho function at an intragenic terminator. - Burns, C M (1995)
Rho-dependent transcription termination at certain terminators in Escherichia coli also depends on the presence of NusG [Sullivan, S. L. & Gottesman, M. E. (1992) Cell 68, 989-994]. We have found that termination at the first intragenic terminator in lacZ (tiZ1) is strongly dependent on NusG when transcription is done in vitro with the concentrations of NTPs found in vivo. With a lower level of NTPs, and consequently a slower rate of RNA-chain growth, Rho causes some termination by itself that is enhanced with NusG. These results suggest that NusG serves to overcome a kinetic limitation of Rho to function at certain terminators. At a second intragenic terminator within the lacZ reading frame (tiZ2) the efficiency of Rho-mediated termination was unaffected by either NusG or by RNA polymerase elongation kinetics. Thus, using purified components and intracellular levels of NTPs, we have confirmed the in vivo finding that certain Rho-dependent terminators also depend on NusG, whereas others do not.